The Effect Of The Problem Based Learning (PBL) Learning Model On Improving Students' Learning Motivation In The Christian Religious Education Subject Of Grade XII - Manullang, Yoel Satria; Siregar, Nurliani; Butarbutar, Imelda (Jurnal Ilmu Pendidikan dan Sosial, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on student learning motivation in Christian Religious Education (CRE) for grade XII TBSM students at SMK Swasta Imelda Medan. The background of this study stems from the low learning motivation of students due to the dominance of conventional methods that tend to make students passive. Therefore, the implementation of an innovative learning model that encourages active participation, critical thinking, and problem-solving is necessary. The research method used was quantitative descriptive with a survey design. The study population was all grade XII TBSM students, and the sample size was 21 students. The data collection instrument was a learning motivation questionnaire that had undergone validity and reliability tests. Data analysis techniques were simple regression, correlation coefficient, coefficient of determination, and significance tests. The results showed a positive and significant effect between the implementation of the PBL model and student learning motivation. This is evidenced by the correlation coefficient of 0.59 indicating a strong relationship, and the calculated t (3.185) > t (2.093) at the 0.05 significance level. Thus, the implementation of PBL can increase student learning motivation in Christian Religious Education at Imelda Private Vocational School, Medan. The coefficient of determination is 34.81%, which shows that Problem Based Learning (PBL) has an influence on students' learning motivation of 34.81%.